Weight Gain Following Kangaroo Mother Care in Low Birth Weight Infants at Bayu Asih General Hospital - Fitri Rahmawati; Rudi Karmi; Damai Yanti (STIKes Budi Luhur Cimahi, 2026)
Kangaroo Mother Care (KMC) supports thermoregulation, breastfeeding, and physiological adaptation in low birth weight (LBW) infants. This study evaluated changes in body weight following a seven-day KMC program in the Neonatal Unit of Bayu Asih General Hospital, Purwakarta, from January to February 2026. A pre-experimental one-group pretest-posttest design was used with total sampling of 15 stable LBW infants. Most infants were born at 35 or 36 weeks of gestation (5 infants [33.3%] in each gestational age group). Mothers performed nurse-supervised KMC for 1–2 hours daily. Infant body weight was measured using a calibrated digital scale before the intervention and on day 7. The mean baseline body weight was 1,625.0 ± 152.4 g, with a median of 1,550 g. After KMC, the mean body weight increased to 1,805.3 ± 169.9 g, with a median of 1,725 g. The mean weight gain was 180.3 g, the median difference was 175 g, the relative increase was 11.3%, and the average daily weight gain was approximately 25 g/day. The Wilcoxon signed-rank test demonstrated a statistically significant difference between pre- and post-intervention body weight (p = 0.001). An exact paired 95% confidence interval and rank-based effect size could not be calculated because the retained analysis output did not include the standard deviation of the paired differences or the Wilcoxon Z statistic. Kangaroo Mother Care was associated with short-term body weight gain in stable LBW infants. However, causal interpretation should be made cautiously because of the absence of a control group and the potential influence of unmeasured feeding practices and other co-interventions.